Spartin recruits PKC-ζ via the PKC-ζ interacting proteins ZIP1 and ZIP3 to lipid droplets. - Urbanczyk, Andreas; Enz, Ralf (Journal of Neurochemistry, 2011)
Protein kinase C-ζ interacting proteins (ZIP1-3) recruit the enzymatic activity of the atypical protein kinase C isoforms PKC-λ/ι or PKC-ζ to target proteins. In this study, we searched for binding partners of ZIP3 in the CNS and identified spartin, a multifunctional protein that is mutated in spastic paraplegia type 20. In transfected cells, spartin was present on the surface of lipid droplets (LD), whereas ZIP proteins appeared in intracellular speckles. In the presence of spartin, ZIP1 and ZIP3 were translocated to spartin-positive LD. This translocation was mediated by amino acids 196-393 of spartin that interacted with an N-terminal region of ZIP proteins. Furthermore, ZIP proteins interacted simultaneously with spartin and PKC-ζ, resulting in an enrichment of PKC-ζ on spartin/ZIP-labelled LD. Without spartin, neither ZIP proteins nor PKC-ζ were detected on LD. Interestingly, the presence of the spartin/ZIP/PKC-ζ complex increased LD size. This effect was most pronounced upon incorporation of the ZIP3 isoform into the trimer. Finally, we co-localized spartin, ZIP proteins and PKC-ζ in axon terminals of neurons in the mammalian retina. In summary, we describe spartin as new binding partner of the ZIP/PKC-ζ dimer that recruits PKC-ζ to LD and show that the expressed ZIP isoform regulates LD size. © 2011 The Authors. Journal of Neurochemistry © 2011 International Society for Neurochemistry.
UnivIS-Import:2015-04-14:Pub.2011.med.IB.profes_1.sparti
Keywords: lipid droplets; p62; protein kinase C-ζ interacting protein; retina; sequestosome-1 (SQSTM1); SPG20